The first validation of the Functional Assessment of Cancer Therapy Hepatobiliary (FACT-Hep) for evaluating health-related quality of life (HRQOL) in patients with advanced-stage intrahepatic cholangiocarcinoma (biliary tract cancer) - Teerachat Saeheng; Nisit Tongsiri; Kesara Na-Bangchang (PLoS ONE, 2025)
Background The FACT-Hep questionnaire has been used to evaluate the health-related quality of life (HRQOL) in various types of hepatobiliary cancer. Nevertheless, the application in intrahepatic cholangiocarcinoma (iCCA) has been limited. The study aimed to validate the applicability of FACT-Hep as a reliable tool for evaluating HRQOL in patients with advanced-stage iCCA. Methods Atractylodes lancea capsules were tested for efficacy and safety in a randomized, controlled phase IIA. Internal consistency, intraclass correlation, test-retest reliability, discriminant and convergent validity, and FACT-Hep score-clinical response connection were assessed. Results Thirty-nine patients qualified for the research. Cronbach’s alpha coefficients > 0.7 showed internal consistency for all subscale items from baseline (day 1) to 90 days. For ICC, convergent, and discriminant validity, all items except the HepCS subscale were reliable. Patients with ECOG scores of 0–1 or 2 had significantly different HepCS subscale values—calculated effect size for subscale score change over time. FACT-G and FWB differed significantly in low-dose group 1. At 3-month, 1-month, and 2-month follow-ups, Group 2 (high dose) patients had significant differences in FACT-Hep, TOI, and HepCS. The effect size was the same in Group 3 (untreated). Group 1 and 2 non-progressive patients exhibited lower FWB and EWB scores than progressive patients. The treated survivors had lower FACT-Hep, TOI, HepCS, FWB, and EWB scores than the non-treated survivors, which was linked to AL treatment side effects. Conclusion The FACT-Hep detects changes and is a reliable and valid tool for assessing HRQOL in patients with advanced-stage iCCA.